2012
DOI: 10.5057/kei.11.67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tone Curve and Size on Kansei Evaluation of High Dynamic Range Images - Comparison of Japanese and Chinese Observers

Abstract: The effects of tone curve and display size on Kansei evaluation of High Dynamic Range (HDR) images were investigated with Japanese and Chinese observers. Forty HDR images (5 tone curves x 4 sizes x 2 contents) were evaluated for Kansei impression using a semantic differential (SD) method with 16 Japanese and 16 Chinese observers with normal color vision. For each adjective, the evaluation value was plotted against the average lightness of the tone curve, and the resulting curves were divided into five types: m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The fabric hand space for Japanese participants (Table 4) presented a 3-factor structure, while that of Chinese participants (Table 5) presented a 2-factor structure. This is in line with Ishikawa et al (2012), who analyzed Japanese and Chinese perceptions of high dynamic range (HDR) images and found that Japanese perceptions had a more complex factor structure. Notwithstanding the differences between the two studies, including the difference in stimuli, the findings suggest that knowledge to discern differences in fabric attributes.…”
Section: Intergroup Differences In Fabric Hand Spacessupporting
confidence: 84%
“…The fabric hand space for Japanese participants (Table 4) presented a 3-factor structure, while that of Chinese participants (Table 5) presented a 2-factor structure. This is in line with Ishikawa et al (2012), who analyzed Japanese and Chinese perceptions of high dynamic range (HDR) images and found that Japanese perceptions had a more complex factor structure. Notwithstanding the differences between the two studies, including the difference in stimuli, the findings suggest that knowledge to discern differences in fabric attributes.…”
Section: Intergroup Differences In Fabric Hand Spacessupporting
confidence: 84%
“…In the KANSEI evaluation experiments, sometimes different observer groups show different tendency. 13,14 Majority of our observers is students belonging to the Faculty of Engineering who are naïve for Semantic Differential method, whereas three observers in middle age are experts of color imaging having long experiences for image quality evaluation. However, the data of these specialists do not systematically deviate from the range of naïve young observers.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison between the distributions of chromaticity coordinates in the “blue” images of four blue primaries and the unique hue loci from Ayama and Ikeda's study …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation